EVALUACIÓN DE UN PROCESO TÉRMICO - FOTOCATALITICO PARA LA DESINFECCIÓN DE AGUA PROVENIENTE DE FUENTES NATURALES MEDIANTE EL APROVECHAMIENTO DE LA ENERGÍA SOLAR (2010)
A kind of parabolic cylinder solar collector (CCP) was designed and constructed on a small scale of average concentration of energy, with the intention of decreasing the concentration of coliformes total and fecal present in the water gotten of natural sources of supply by means of the application of thermal processes and thermal photocatalytic (Ti02 Degussa P25) that use the solar radiation. The results of this investigation allow to conclude that though the solar íight for itself has a bactericidal effect, the TÍ02 in presence of solar inactive radiation the coliformes more rapidly using less temperatures compared with the thermal process, which does of this one an effective method for the treatment of the water for human consumption.